2003
DOI: 10.1089/109493103321168009
|View full text |Cite
|
Sign up to set email alerts
|

Model of Problematic Internet Use in People with a Sexual Interest in Children

Abstract: Agencies working with sex offenders are starting to see the emergence of people with a sexual interest in children who meet some of their needs through the use of child pornography, or the seduction of children, through the Internet. While CBT models dominate our understanding of sex offenders, there has been little research into the role that such new technologies may play in offending behavior. Data from the COPINE project has been used to generate a model of such offending behavior that emphasizes the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 28 publications
4
120
0
3
Order By: Relevance
“…These results suggest a small subgroup of deeply invested downloaders among the CP-only suspects, who are at a higher risk to cross the line to the direct victimization (Quayle & Taylor, 2003). In line with Babchishin et al (2014), the results in this subgroup of CP-only suspects suggested greater sexual deviance.…”
Section: Discussionmentioning
confidence: 59%
“…These results suggest a small subgroup of deeply invested downloaders among the CP-only suspects, who are at a higher risk to cross the line to the direct victimization (Quayle & Taylor, 2003). In line with Babchishin et al (2014), the results in this subgroup of CP-only suspects suggested greater sexual deviance.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, in a recent study on offence motivations (Merdian, Boer, Thakker, Wilson, & Curtis, 2013), MOs were found to be more likely than CPOs to self-identify a sexual interest in minors as their main motivation to view child pornography, pointing towards higher endorsement of cognitive distortions relating to children and sex. An alternative explanation can be seen in the hypothesis that distorted cognitions are subject to change as the offender progresses in his offending behaviour (Carr, 2006;O'Brien & Webster, 2007;Quayle & Taylor, 2003), with CPOs and MOs arguably being placed at different stages on the fantasy versus contact-driven offending continuum. For example, Quayle and Taylor (2001) reported the case of a 33-year-old online sex offender, who, while progressing in his behaviour from child pornography consumption to engaging with victims online, also changed his language and self-portrayal from initially presenting himself as a child to that of a sexually aggressive adult, potentially indicating a shift in his cognitive processes.…”
Section: Cognitive Distortions As Potential Facilitators Of Contact Smentioning
confidence: 99%
“…The focus of this study will center on the latter. Quayle and Taylor (2003) performed a study regarding the effect of the Internet on persons that obtain child pornography or attempt to seduce children to meet their sexual needs. They state that we as a society try to understand adults that are sexually interested in children in a cognitive-behavioral way.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few studies have been performed on the actual techniques and characteristics of online predators (Baker, 2002;Quayle & Taylor, 2003). Such studies have shown that adult males usually attempt to lure young girls into participating in sexual activity using various tactics.…”
mentioning
confidence: 99%